LEGAL REASONINGCOURT RULING AGGREGATED THEFT CRIMINAL ACT: Decision Study Number: 37/Pid.B/2019/PN.BMS - Jamaludin; Tata Eliestiana Dyah A (Universitas Islam Negeri Mataram, 2025)
Judges as decision makers need to applylegal reasoningobjectively in order to achieve justice. Weak implementationlegal reasoningcan produce an onvoldoende gemotiveerd decision, such as in the Banyumas District Court Decision Number 37/Pid.B/2019/PN.Bms which is considered inconsistent with the provisions of Article 363 of the Criminal Code. This study aims to determine the basis for the judge's considerations in imposing a sentence for the crime of aggravated theft and to analyze the application of legal reasoning in decision Number 37/Pid.B/2019/PN.Bms. This type of research uses normative legal research using a statutory and case approach. The results of the study indicate that the basis for the judge's considerations in imposing a sentence is in accordance with the criminal procedure law mechanism as regulated in Law Number 8 of 1981, where the judge bases the decision on at least two pieces of evidence and trial facts. The evidence in the form of witness statements, the defendant's statement, and evidence proves that the defendant Saiful Aziz is legally and convincingly guilty of violating Article 363 paragraph (1) 3, 4, and 5 of the Criminal Code. However, the judge was deemed not to have applied legal reasoning in depth because the sentence of 1 year and 2 months imposed did not reflect the severity of the elements fulfilled or the aggravating circumstances proven based on the facts in the trial.